Unions, Equity, and the Path to Renewal - Hunt, Gerald (Relations industrielles / Industrial Relations, 2011)
Unions, Equity, and the Path to Renewal, edited by Janice Foley and Patricia Baker, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Equity; Feminism; International; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z